2016
DOI: 10.1016/s2352-3026(16)30079-5
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban versus warfarin to treat patients with thrombotic antiphospholipid syndrome, with or without systemic lupus erythematosus (RAPS): a randomised, controlled, open-label, phase 2/3, non-inferiority trial

Abstract: SummaryBackgroundRivaroxaban is established for the treatment and secondary prevention of venous thromboembolism, but whether it is useful in patients with antiphospholipid syndrome is uncertain.MethodsThis randomised, controlled, open-label, phase 2/3, non-inferiority trial, done in two UK hospitals, included patients with antiphospholipid syndrome who were taking warfarin for previous venous thromboembolism, with a target international normalised ratio of 2·5. Patients were randomly assigned 1:1 to continue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
252
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(279 citation statements)
references
References 30 publications
9
252
0
7
Order By: Relevance
“…A randomised clinical study comparing rivaroxaban and warfarin in over 100 APS patients with previous VTE showed the endogenous thrombin potential to be increased but the peak thrombin to be reduced in the rivaroxaban arm after 42 days of treatment. 41 The clinical significance of these results is not yet known. No data are available on NOACs in APS patients with arterial thrombosis; warfarin remains the anticoagulant of choice for both venous and arterial thrombosis in the APS setting.…”
Section: Cancermentioning
confidence: 98%
“…A randomised clinical study comparing rivaroxaban and warfarin in over 100 APS patients with previous VTE showed the endogenous thrombin potential to be increased but the peak thrombin to be reduced in the rivaroxaban arm after 42 days of treatment. 41 The clinical significance of these results is not yet known. No data are available on NOACs in APS patients with arterial thrombosis; warfarin remains the anticoagulant of choice for both venous and arterial thrombosis in the APS setting.…”
Section: Cancermentioning
confidence: 98%
“…Ongoing clinical trials to determine the safety and efficacy of NOACs in APS may lead to additional clarity. 14,18 This uncertainty should be discussed with the patients who should also be involved in the decisionmaking process.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the RAPS trial, a randomized controlled, open label non-inferiority trial that compared rivaroxaban with warfarin to treat patients with thrombotic antiphospholipid syndrome, with or without systemic lupus erythematosus (RAPS) 14 was recently published. The investigators concluded that the NOACs are non-inferior to VKAs.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint, the percentage change in endogenous thrombin potential (ETP) from randomization to day 42, was higher in the rivaroxaban group together with markedly lower peak thrombin generation, the most sensitive marker of thrombin formation. No VTE episodes or serious bleeding were reported, leading to the conclusion that rivaroxaban "could be an effective and safe alternative" in thrombotic APS [47]. Although the size of the study groups was limited and the observation period short, the RAPS study provided valuable confirmation that the impact of rivaroxaban on blood coagulation is comparable to warfarin with a target INR of 2.5 in patients with various forms of APS.…”
Section: Antiphospholipid Syndromementioning
confidence: 96%
“…An open-label, randomized, controlled trial -rivaroxaban in antiphospholipid syndrome (RAPS) study, performed on thrombotic APS patients allocated to warfarin or rivaroxaban 20 mg daily, was published in September 2016 [47]. The primary endpoint, the percentage change in endogenous thrombin potential (ETP) from randomization to day 42, was higher in the rivaroxaban group together with markedly lower peak thrombin generation, the most sensitive marker of thrombin formation.…”
Section: Antiphospholipid Syndromementioning
confidence: 99%